An overview of islamic welfare and mobilization of e-Sadaqah Jariah / Noor Saliza Zainal ...[et al.]. - Zainal, Noor Saliza; Awang @ Ab.Rahman, Nurul Hidayah; Mustafa @ Busu, Zanirah; Noor Zainan, Nurul Izzah; Ismail, Mohd. Khairul Anuar; Nik Din, Nik Muniyati (2021)
This paper reviews the concept of welfare, sadaqah, and the application of e-Sadaqah Jariah in Malaysia. Welfare is defined as a situation of a good life for an individual or society as a whole. As a religion of rahmatan lil alamin (blessing for all), Islam provides various ways to tackle the situation. One of the solutions for the poor and have-nots is sadaqah (charity) or sadaqah Jariah (ceaseless charity), a voluntary deed recommended for all Muslims. Nowadays, due to the advanced technology, especially in the era of Industrial Revolution 4.0, the usage of online charity, popularly known as e-Sadaqah is more popular than the traditional form. The objectives of this study have twofold. Firstly, is to discuss and reemphasize the importance of sadaqah jariah. Secondly, it is to clarify how to mobilize e-Sadaqah Jariah in uplifting the less fortunate in the present society. The scope of the study is to discuss the concept of sadaqah jariah and the application of e-Sadaqah Jariah in Malaysia. This study is only conceptualized-library research. Thus, the sources of information are obtained from secondary sources such as journals, books, and the Internet. The study found that e-Sadaqah Jariah is very important and highly recommended in Islam. Other than that, the study also found that the mobilization of e-Sadaqah is applicable all over the place and very useful. Its application will facilitate the donors and speed up the collection of sadaqah to be distributed to the needy and poor.